IMPLEMENTASI AKUNTANSI SYARI’AH PADA PEMBIAYAAN MUDHARABAH BERDASARKAN PSAK NO. 105 PADA KJKS BMT AL-HAYYU KOTA BATAM - Effendi, Syahril (MEASUREMENT : Jurnal Program Studi Akuntansi, 2014)
This research is motivated by. The development of the banking industry today is increasingly manifest improvement in creating a wide range of financial products that can mobilize and execute national financial resources more efficiently. Financial products offered by banks in mobilizing funds increasingly diverse society. Today many financial institutions or banks raced each other to provide the best service and convenience for its customers. Indonesia's population of Muslim majority and many members of the community who are reluctant associated with conventional banks, is a great potential for financial institutions based on Islamic principles. Thus stems from the desire to further improve the gait of Muslims in building the national economy including the desire to make money financial institutions operating under Islamic principles amid competition from conventional banks.This study aims to investigate the implementation of Mudaraba financing and implementation of SFAS 105 on KJKS BMT AL-Hayyu. This type of research used in this study is a qualitative study, using primary data with interviews directly on the object of research and secondary data, with books, data and reports relating to the object of research. The analysis used in this study is a descriptive analysis method. Results of research conducted showed that Mudaraba Accounting Treatment applied by KJKS BMT Al-Hayyu not say fit because there are not implemented, there is the disclosure, presentation, recognition and measurement. But on the characteristics of SFAS 105 had no applied KJKS BMT Al HayyuKeywords: Mudarabah, SFAS 105